معيارالإسناد بين المحدثين والمؤرخين)الإمام الزهري كالنموذج(دراسة تحليلية (Al Basirah, 2020)
The issue of isnad (chain of transmitters) is one of the big issues whichhave been discussed on a large scale between muslim historians andmuhaditheen (traditionists). The problem actually lies in that the narratives oflife of Prophet Muhammad PBUH divide into two major kinds. Some of themare related to his ritual and spiritual life which are called ahadith ul aqa’id walahkam. The other kind of narratives belongs to the general info about his lifeand character. The muhaditheen take care of ahdith ul aqa’id wal ahkam. Onthe contrary ،the historians are concerned for the other kind of narratives.The muhaditheen feel obliged when they narrate a holy prophet’snarrative to mention a complete isnad by ensuring certain conditions in itstransmitters (ruwat) which are declared for them to be authentic. They try tostrictly apply all rules from all aspects on every part of isnad. Contrariwise ،thehistorians do not bind themselves with the standards and principles set bymuhaditheen. They see that the historical narratives are totally different fromthe nature of narratives of aqa’id and ahkam. They think that they can’t beover strict in the case of historical narrative; otherwise they will lose and missa huge number of them ،and consequently ،they can’t explain the life ofProphet Muhammad (SAW )explicitly.In this article ،I have tried to express both points of view in this regard ،and to clarify to what extent we can apply muhaditheen’s rules regarding isnadover historical narratives to purify their strong from weak one. I have chosenAl-Waqidi as the model for this article because he is the most disputed figurein this regard. Most of criticism he faced from the muhaditheen’s critique wasrelated to isnad’s issues.
Keywords: Isna'd, Marasi'l, Tafarrud, Historian, Muhaddithi'n, Zuhri